2D Hall-MHD investigation of the magnetic pressure balance during merging start-up in spherical tokamaks. (21st October 2021) - Ahmadi, T.; Ono, Y.
Abstract: In this work, the formation and merging of two spherical tokamak (ST) plasmas have been studied by the mean of the 2D Hall-MHD simulation. It was found that during the ST plasma formation, an internal toroidal field is formed due to the changes in the flux surface. The expanding force of this toroidal field pushes the formed STs toward the mid-plane just after the pinch-off, while the magnetic tension and mutual attraction of plasma toroids mainly drive the merging at the mid-plane. During the merging, the internal toroidal field doubles inside the separatrix due to the shrinking of the flux surface while the total toroidal and poloidal fluxes are conserved. After the merging, the single plasma goes through a relaxation process, reaching a force-free state.